Efficacy and safety of intragastric balloon for obesity in Korea - Kwang Gyun Lee; Seung-Joo Nam; Hyuk Soon Choi; Hang Lak Lee; Jai Hoon Yoon; Chan Hyuk Park; Kyoung Oh Kim; Do Hoon Kim; Jung-Wook Kim; Won Sohn; Sung Hoon Jung (Clinical Endoscopy, 2023)
Background/Aims Intragastric balloon (IGB) is the only available endoscopic bariatric and metabolic therapy in Korea. End-ball (Endalis) has the longest history of clinical use among the IGBs available in Korea. However, little clinical data on this system have been reported. In this study, we aimed to evaluate the efficacy and safety of End-ball in Korea. Methods We performed a retrospective cohort study of patients who underwent IGB insertion (End-ball) from 2013 to 2019. Demographic and anthropometric data were collected. The efficacy and safety of IGB treatment were analyzed. Results In total, 80 patients were included. Mean age was 33.7 years and 83.8% were female. Initial body mass index was 34.48±4.69 kg/m2. Body mass index reduction was 3.72±2.63 kg/m2 at the time of IGB removal. Percent of total body weight loss (%TBWL) was 10.76%±6.76%. Percentage excess body weight loss was 43.67%±27.59%. Most adverse events were minor, and 71.4% of participants showed nausea, vomiting, or abdominal pain. Conclusions IGB treatment showed good efficacy and safety profile in Korean patients with obesity. In terms of %TBWL and percentage excess body weight loss, the efficacy was similar to that in the Western population.